New regulatory mechanisms in the biosynthesis of pheomelanins: rearrangement vs. redox exchange reaction routes of a transient 2H-1,4-benzothiazine-o-quinonimine intermediate - Napolitano, Alessandra; Di Donato, Paola; Prota, Giuseppe (Biochimica et biophysica acta, 2000)
Pheomelanins, the typical epidermal pigments of red haired, Celtic-type Caucasians, arise from oxidative cyclization of cysteinyldopas, mainly the 5-S-isomer CD, via 1,4-benzothiazines. However, the mechanism and the relative yields of formation of these intermediates have remained poorly defined. We have now examined the course of the oxidation of CD at physiological pHs, under different reaction conditions. Surprisingly, a consumption of CD far exceeding the stoichiometry of the oxidant was observed at low oxidant-to-substrate ratios, low temperatures and high substrate concentrations. The yields of the 3,4-dihydro-1,4-benzothiazine-3-carboxylic acid DHBCA vs. the non-carboxylated analogue DHB in the oxidation mixture, after NaBH4 reduction, were also found to depend markedly on the reaction conditions. Based on these and other results, a reaction scheme is proposed involving a transient o-quinonimine generated by oxidative cyclization of CD to which three different paths are offered, namely redox exchange with CD to give DHBCA (path A) or intramolecular rearrangement with (path B) or without (path C) decarboxylation, leading to the benzothiazine BTZ and the 3-carboxy analogue BTZCA, respectively. The relative operation of path A vs. path C was assessed by deuterium labeling experiments. These findings point to new mechanisms of regulation of the initial steps of pheomelanogenesis, bearing significant implications on the structure of the final pigment.